COMPUTER SIMULATION OF BENDING CIRCULAR SANDWICH PLATES USING ANALYTICAL AND NUMERICAL APPROACHES - Kudin, A. V.; Choporov, S. V. (Radio Electronics, Computer Science, Control, 2014)
The paper describes equations of circular symmetrical sandwich plates bending for plates with isotropic outer layers and nonlinear elastic filler. Two computer models of circular sandwich plates are proposed: 1) analytical model on the basis of Maple CAS, 2) threedimensional FEM-model. We compare results of analytical model with results of numerical simulation using two problems: 1) the problem of axisymmetric transverse bending of a sandwich plate, 2) the problem of axisymmetric transverse bending of a single-layer plate with linear and nonlinear formulation. The first section of the article describes basic differential equations and analytical model constructing method. FEM-model is described in the second section. Numerical results of computer simulation are showed in the last section of the article.